Pseudorotation in Jahn-Teller systems - Sindi, Lubna (2008)
The molecular shape of any nonlinear molecule can be strongly influenced by the coupling between electrons and vibrations (vibronic coupling) via the Jahn-Teller (JT) interaction within the molecule. This influence appears as a distortion of the symmetrical shape of the original molecule. In such molecules, the adiabatic potential energy surface (APES) possesses either a trough of minimum-energy points or several isoenergetic minima ('wells') depending on the nature of the interactions present.